Does the Association Between Age and Major Illness Vary by Healthcare System Quality?. (December 2019) - Andersson, Matthew A.; Wilkinson, Lindsay R.; Schafer, Markus H.
This study builds on research into global aging, by offering a multiple-indicator test of whether national healthcare system quality modifies the association between age and major illness. Recent individual-level data on morbidity among respondents aged 50 or older (16 countries; 2014 European Social Survey) are merged with nation-level healthcare indicators. Healthcare system quality is assessed using a subjective, evaluation-based approach and an objective, attributable-mortality approach. Lagged nation-level economic and health indicators are controlled to help isolate healthcare system effects. Results across subjective and objective approaches to healthcare system quality are strikingly consistent. While older individuals showed approximately a 10% reduction in probability of major illness when residing in countries with higher healthcare quality, associations between age and morbidity indices combining number and severity of illness showed greater modification by healthcare quality, with reductions around 18%. Taken together, results are suggestive of healthcare's protective role in reducing age-related illness and disability.